Dialog Tentang Manusia Dalam Yak?a Pra?na (Dialog Yak?a Dengan Yudhi??hira) - I Putu Ariyasa Darmawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Yak?a Pra?na is a question from Yak?a to Yudhi??hira. The Yak?a Pra?na as part of the Veda Sm?ti, namely the Itih?sa, consists of 34 lokas containing dialogues between Yudh??hira and the Yak?a about the Vedas and humans. The type of research used in this study is qualitative research, the type of data in this study is qualitative data. The primary data source in this study is the Yak?a Pra?na text.Studying or understanding the Veda cannot be done haphazardly, it must be started gradually from the Itih?sa and Pur??a, as described in Vayu Pur??a 1.20 and Sarasamuccaya verse 39, that the Veda should be perfectly studied by studying the Itih?sa and Pur??a.The dialogue between the Yak?a and Yudhi??hira regarding the teachings of dharma, the virtues of the Vedas, the obligations of Color Chess, the teachings of the yajas, humans and the dharma of life is very simple but Yudhi??hira is able to grasp the meaning of the question, so that the question is answered with meaning. The Yak?a is none other than the incarnation of the Dharma God in disguise to test Yudhi??hira's abilities regarding Vedic teachings and humans.Some of the topics discussed in human philosophy include human nature as a person, body and soul, freedom, knowledge, human social dimensions, culture, language, history, and work. Several streams in human philosophy include the flow of materialism, idealism, dualism, vitalism, existentialism, structuralism, and postmodernism.Keywords: Man, Yak?a, Yudhi??hira